Standardisation of Factor VIII and von Willebrand Factor in Plasma: Calibration of the 4th International Standard (97/586) - Hubbard, Anthony R.; Rigsby, Peter; Barrowcliffe, Trevor W. (Thrombosis and Haemostasis, 2001)
The 4th International Standard (IS) Factor VIII/von Willebrand Factor (FVIII/VWF) plasma was calibrated in 25 laboratories by assay against the 3rd IS plasma and fresh normal plasma pools. Five parameters were measured, FVIII:coagulant activity (FVIII:C), FVIII:Antigen (FVIII:Ag), VWF:Antigen (VWF:Ag), VWF:Ristocetin Cofactor (VWF:RCof), and a new parameter, VWF:collagen binding (VWF:CB). Mean potency estimates for the 4th IS, calculated relative to the 3rd IS, were significantly greater than the mean estimates calculated relative to the fresh normal pools by 15, 14 and 20% respectively for FVIII:C, VWF:Ag and VWF:RCof. These results indicate a drift in the International Unit away from the fresh plasma unit. Partial rectification of this drift was achieved by assigning the mean of the estimates calculated relative to the 3rd IS and the fresh plasma pools, i.e. FVIII:C 0.57 IU/ampoule, VWF:Ag 0.79 IU/ampoule and VWF:RCof 0.73 IU/ampoule. This represents a shift in the IU between the 3rd and 4th IS of 7.5% for FVIII:C, 7% for VWF:Ag and 10% for VWF:RCof. Mean estimates of FVIII:Ag relative to the 3rd IS and the fresh normal pools agreed to give an assigned value of 0.89 IU/ampoule. Excessive inter-laboratory variability and a low number of estimates (n = 6) precluded the assignment of a potency for VWF:CB. The 4th IS Factor VIII/VWF plasma (97/586) was established in October 1998.
Keywords: Factor VIII; von Willebrand factor; International Standard; blood plasma